Major root endodontic treatments: a systematic review - Santos, Larissa Mylena Fernandes dos (2024)
Introduction: In the root canal treatment scenario, irrigation is one of the most important aspects of the biomechanical preparation of the root canal. A condition for successful endodontic retreatment is adequate cleaning of the root canals, therefore, special attention should be paid to the technique used to remove the filling material, the most commonly used being cement, pastes, and gutta-percha cones. Objective: This study aimed to present the main root endodontic treatments to analyze and compare the techniques for removing pulp tissue debris resulting from root preparation and microorganisms from the canals of the root canal system, seeking complete cleaning and asepsis. Methods: The PRISMA Platform systematic review rules were followed. The search was conducted from April to July 2024 in the Scopus, PubMed, Science Direct, Scielo, and Google Scholar databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results and Conclusion: 129 articles were found, 39 were evaluated and 21 were included in this systematic review. Considering the Cochrane tool for risk of bias, the global assessment resulted in 25 studies with a high risk of bias and 27 studies that did not meet GRADE. Most studies showed homogeneity in their results, with X2 =91.5% >50%. It was concluded that the system of root canal instrumentation with rotary files maintains the quality of root preparation and, at the same time, reduces the number of files required to obtain a canal, which would consequently reduce the operative time and also considerably reduce the risk of torsion fracture within the root canal than with files. Irrigation plays a fundamental role in the success of endodontic treatment. Although hypochlorite is the most important irrigant solution, no irrigant can perform all the tasks required by irrigation. A detailed understanding of the mode of action of various solutions is important for optimal irrigation. Within the limitations of this study, the use of the self-adjusting file with the combination of EDTA and NaOCl improved Ca(OH)2 removal. Passive ultrasonic irrigation and the self-adjusting file were more effective in removing Ca(OH)2 from the lateral sulci in the apical parts of the root canal than the EndoVac and conventional syringe irrigation systems.